Persistent elevation of plasma markers of cellular senescence after hip fracture: a pilot longitudinal study - Eric J. Lenze; Ginger E. Nicol; George A. Kuchel; Michael S. Avidan; Breno S. Diniz (Frontiers in Aging)
IntroductionHip fractures may result from and contribute to accelerated biological aging. We aimed to evaluate the impact of hip fracture and its surgery on the senescence-associated secretory phenotype (SASP) index, a composite of peripheral protein markers where higher scores are thought to indicate greater levels of cellular senescence and accelerated aging.MethodsWe examined the SASP index in plasma over 12 weeks post-surgery and its prediction of long-term post-surgical functional outcomes. We included 60 older adults: 20 recruited immediately after hip fracture surgery, and 40 comparison individuals who were either healthy or suffering chronic psychosocial stress (caregiving). We assessed 22 SASP biomarkers and calculated the SASP index score for each hip fracture participant immediately following fracture surgery and 4 and 12 weeks later. Functional recovery was assessed at 12, 26, and 52 weeks after hip replacement surgery.ResultsThe hip fracture group had higher SASP index scores than the comparison groups, after adjusting for potential confounding variables (p = 0.021). SASP index scores in hip fracture patients increased further by week 4 after surgery (p < 0.001), declining by week 12 but remaining elevated overall. However, the SASP index scores were not significantly associated with functional recovery after hip replacement surgery at 26 or 52 weeks after surgery. In conclusion, after hip fracture surgery SASP scores are elevated, continue to rise over time, and do not return to normal by 12 weeks post-surgery.DiscussionOur findings support the need to investigate this phenomenon of post-operative senescence, including whether novel interventions such as senolytics would help older adults facing major surgery.